2003
DOI: 10.1002/bit.10818
|View full text |Cite
|
Sign up to set email alerts
|

Swirling flow implementation in a photobioreactor for batch and continuous cultures of porphyridium cruentum

Abstract: Light is the main limiting factor in photoautotrophic-intensive production of microorganisms, and improvement of its use is an important concern for photobioreactor design and operation. Swirling flows, which are known to improve mass and photon transfers, were applied to annular light chambers of a photobioreactor and studied by simulation and microalgal culture. Two hydrodynamic conditions were compared: axial flow generating poor radial mixing, and tangential flow generating three-dimensional swirling motio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…This could be an option for improved annular reactors, although the technical expenditure is quite high. The employment of tangential flow to generate a threedimensional swirling motion is given by [33].…”
Section: Interactions Between Physiology and Reactor Designmentioning
confidence: 99%
“…This could be an option for improved annular reactors, although the technical expenditure is quite high. The employment of tangential flow to generate a threedimensional swirling motion is given by [33].…”
Section: Interactions Between Physiology and Reactor Designmentioning
confidence: 99%
“…Barahona and Rorrer (2003) have shown that bioreactor tissue culture can be used successfully for production of secondary metabolites from marine algae within a controlled environment using species of Ochtodes secundiramea and Portieria hornemannii. Muller-Feuga et al (2003) have implemented swirling flow in a photobioreactor for batch cultures of the red alga Porphyridium cruentum. Since light is one of the principal factors for the growth of photoautotrophic organisms such as marine algae, swirling-flow modifications help in moving biomass into areas with higher Fig.…”
Section: New Avenues Of Researchmentioning
confidence: 99%
“…12.12A) or another type of swirling flow inducer (Fig. 12.12B) can enhance the turbulence mixing degree in the photobioreactor [60,66,67,83,84,85,86,87]. In photobioreactors operated with gas-liquid two-phase flow, the turbulent mixing is bubble induced [88].…”
Section: Novel Photobioreactor Configurationsmentioning
confidence: 99%